1985
DOI: 10.1016/0002-9416(85)90233-7
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and dental changes following functional regulator therapy on class II patients

Abstract: Craniofacial growth in 100 patients treated with the functional regulator of Fränkel for about 24 months was compared with craniofacial growth seen in a matched group of untreated persons with Class II malocclusion. Both conventional and geometric cephalometric analyses were used to evaluate the skeletal and dental adaptations. This study shows several clear effects of treatment in either of two age ranges considered. The principal skeletal effect was advancement of the mandible along the direction of the faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
3
42

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(160 citation statements)
references
References 28 publications
10
105
3
42
Order By: Relevance
“…This result was in agreement with several authors [8,16], who found no evidence of increased facial height during treatment with various functional appliances. There were no significant differences between the removable and fixed appliance groups, which suggest that increase in the skeletal vertical dimension should be related to growth rather than to treatment with different types of functional orthopedics [17].…”
Section: Skeletal Changessupporting
confidence: 94%
See 1 more Smart Citation
“…This result was in agreement with several authors [8,16], who found no evidence of increased facial height during treatment with various functional appliances. There were no significant differences between the removable and fixed appliance groups, which suggest that increase in the skeletal vertical dimension should be related to growth rather than to treatment with different types of functional orthopedics [17].…”
Section: Skeletal Changessupporting
confidence: 94%
“…This is against other investigators who claim that functional appliances produce lingual tipping of the upper incisors [16,21].…”
Section: Dentoalveolar Changescontrasting
confidence: 67%
“…15,[17][18][19][20][21][22] The present results indicate that an orthopedic effect on mandibular growth can be achieved even earlier, in the early mixed dentition. In an analysis of treatment effects of the FR-2 appliance of Frä nkel, McNamara et al 18 found that the growth response was greater in the older patients with a starting age of 11.5 years compared to the younger patients with a starting age of 8.5 years. The annual growth increment was 1.8 mm in the older group and 1.2 mm in the younger group.…”
Section: Discussionsupporting
confidence: 61%
“…The annual growth increment was 1.8 mm in the older group and 1.2 mm in the younger group. 18 The growth rate in the present treatment sample was 1.2 mm per year. These figures are in line with suggestions that the best response to functional therapy in terms of mandibular growth rate is achieved at or near the peak of the pubertal growth spurt.…”
Section: Discussionmentioning
confidence: 50%
“…A maximum of 5-15% increase in mandibular length by stimulating condylar growth can be expected in experimental animals under controlled conditions and during periods of active growth. 25 Animal experimental research is often cited as evidence but cautious interpretation of the results is required before it is applied to patients.…”
Section: The 'Orthopaedic Effect' -Can We Influence Growth?mentioning
confidence: 99%